The effect of raised the data envelope and benchmarking technique on competitive advantage : Applied research in a group of Iraqi private banks (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The current research aims to reveal the impact of the data envelope and benchmarking technique in the competitive advantage of a group of private Iraqi banks. In this work, the problem was that the banks of the research sample (Union Bank, Mansour Investment Bank, Development and Finance Bank for Investment and Finance, Middle East Bank, and Iraqi Investment Bank) do not apply the data envelope and the reference comparison technique proactively and enter them in all their banking operations adopting (DEAP.2.1, SPSS). This impacts their competitive advantage compared to international banks. The study was based on the basic premise that the possibility of applying the reference comparison technique and the method of analyzing the data envelope contributes to enhancing the competitive advantage of the commercial banks of the research sample, and it has been reached through the research to a set of conclusions, foremost of which is that the use of the data envelope and the reference comparison technique contributes to achieving competitive advantage. This study recommends increasing the percentage of banks' use of the data envelope and benchmarking to raise their sales to achieve competitive advantage.